4 1 ( y ′ ) 2 − 2 1 y ′ = y 2 − y
The non-linear differential equation above admits two non-zero solutions y 1 and y 2 . Suppose that y 1 ( 0 ) = y 2 ( 0 ) = 2 .
What is y 1 ( 1 ) + y 2 ( 1 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thanks for bringing up a discussion @Michael Mendrin . I'll pick up where you left off!
Case I: 2 1 y ′ − y = 0 . In this case, we can solve using separation of variable methods . 2 1 y ′ − y = 0 ⟶ y d y = 2 d x ⟶ ln ( y ) = 2 x + C ⟶ y = C e 2 x In this instance, y ( 0 ) = 2 implies that our first non-trivial solution is y 1 = 2 e 2 x .
Case II: 2 1 y ′ − y = 0 . In this case, we safely divide through by 2 1 y ′ − y , which returns the equation 2 1 y ′ + y = 1 . Using the method of separation of variables again we can easily find y 2 :
2 1 y ′ + y = 1 ⟶ 1 − y d y = 2 d x ⟶ − ln ∣ 1 − y ∣ = 2 x + C ⟶ y = C e − 2 x + 1
Here, y ( 0 ) = 2 implies that our second non-trivial solution is y 2 = e − 2 x + 1 . So our final answer is
y 1 ( 1 ) + y 2 ( 1 ) = 2 e 2 + e − 2 + 1 ≈ 1 5 . 9 1 3
Log in to reply
What I can say is that if, for example, that 4 1 was 3 1 instead, this thing would just blow up. I'd hate to try to imagine the full solution.
Let u = y ′ and multiply the DE through by 4 to obtain:
u 2 − 2 u − 4 ( y 2 − y ) = 0 ⇒ u = 2 2 ± 4 + 1 6 ( y 2 − y ) = 2 2 ± 2 4 y 2 − 4 y + 1 = 1 ± ( 2 y − 1 ) 2 = 1 ± ( 2 y − 1 )
or y ′ = 2 y , 2 − 2 y . Integrating both DE's now produces:
l n ∣ y 1 ( x ) ∣ = 2 x + C 1 ; y 1 ( 0 ) = 2 ⇒ C 1 = l n ( 2 ) ⇒ y 1 ( x ) = 2 e 2 x
− l n ∣ 1 − y 2 ( x ) ∣ = 2 x + C 2 ; y 2 ( 0 ) = 2 ⇒ C 2 = 0 ⇒ y 2 ( x ) = 1 + e − 2 x
Finally, y 1 ( 1 ) + y 2 ( 1 ) = 2 e 2 + 1 + e − 2 ≈ 1 5 . 9 1 3 .
You missed a third solution the constant function y=1
Problem Loading...
Note Loading...
Set Loading...
This quickly factors as follows, into two easily solved first order differential equations
4 1 ( y ′ ) 2 − y 2 = ( 2 1 y ′ + y ) ( 2 1 y ′ − y ) = 2 1 y ′ − y
The art of solving differential equations is still too much like alchemy, too much depends on luck